Procalcitonin Level Recommendation as a Predictive Biomarker for Post-Operative Complication in Colorectal Cancer - Budhi Ida Bagus (New Advances in Medicine and Medical Science Vol. 6, 2023)
Although it may not be supported in tertiary hospitals, particularly in developing nations, C-reactive protein (CRP) has been announced as a new biomarker parameter of post-operative complications and has already been widely used in routine clinical practice. Early research found that when predicting the post-operative morbidity following major gastrointestinal surgery, the sensitivity and specificity of the CRP level are better predictive indicators than the WBC level alone. During major gastrointestinal surgery (resection of colorectal cancer), anastomosis leak was reported in 7 to 10% of cases. Clinical findings in the early stages of anastomosis leak are frequently insufficient to establish this complication and are occasionally mistaken as post-operative pain. Procalcitonin (PCT) is one of the potential biomarkers that has been announced recently as a post-operative complication examination.